Relationship between phosphorus intensity and capacity parameters in Finnish mineral soils: II Sorption-desorption isotherms and their relation to soil characteristics - Hartikainen, Helinä (Agricultural and Food Science, 1982)
The relationship between P intensity and capacity parameters in 104 mineral soil samples was studied by means of sorption-desorption isotherms of two types. In the isotherm A the P exchange was expressed as a function of P concentration in the initial solution, in the isotherm B as a function of P concentration in the final equilibrium solution. Both isotherms conformed to the equation y = a + bx, where y stands for the amount of P sorbed or desorbed and x the P concentration in the solution. In the isotherm A the constant a is the intensity factor expressing the amount of water soluble P at a given soil-solution ratio. The term a in the isotherm B, on the contrary, was only poorly related to water soluble P in soil. In both isotherms the slope b of the line seemed to be most effectively affected by oxalate extractable Al. The relative importance of oxalate soluble Fe appeared to be greater in affecting the effectiveness of sorption-desorption reactions than in affecting the buffer reactions. However, the slope b of both isotherms was found to be a semi-intensive parameter: it was quite markedly dependent also on soil characteristics which control the level of water soluble P in soil. The ratio of the term —a to b (termed as EBS or EPC), expressing the zero point of net P exchange, varied from 0.003 to 13.89 mg P per liter, the lowest values tending to be in the heavy clay soils and the highest ones in the non-clay soils. The practical significance of this quantity was discussed.